Anteseden Perilaku Membayar Zakat pada Badan Amil Zakat Nasional di Lumajang (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2020)
This research explains the antecedents of the behavior of paying zakat on the National Zakat Agency by developing Theory of Planned Behavior. The purpose of this study was to determine the effect of attitude, subjective norm, perceived control, trust and religiosity on intention to pay zakat of the Lumajang community at the Amil Zakat Board. This study used a questionnaire that was distributed with accidental sampling technique. The samples in this study were 100 Muzakki and Muzakki Candidates at Baznas in Lumajang. Analysis test using multiple regression. The results of this study indicate that the higher the attitude, subjective norms, trust and religiosity, the more intention to pay zakat on the Amil Zakat Board will increase. In contrast to the perceived control, it has a significant negative effect on intention to pay zakat. This is because the desire of muzakki to distribute zakat directly is greater than to distribute zakat to the amil zakat agency because it is in accordance with their own wishes. The implication of this research is to change the individual's unique behavior of BAZNAS to take a persuasive approach so that gradually the public's perception of the amount of reward if they distribute their zakat directly can change.